A comparative study of the potassium bromate (KbrO3) content of pan de sal from selective bakeries in Iloilo City. - Arbes, Kristin Maria S. (Iloilo City UPHSI, 2004)
Potassium bromate (KBr0^3) is an essesntial ingredient in making bread. It is used in the treatment of flour, to give it the characteristic that makes bread rise in the oven, and in creating a good texture in the finished product. However, studies show that KBrO3 is carcinogenic, causes chromosomal aberrations, and renal cell tumors. In contrast, it is particularly safe to use KBrO3 in baking provided none or minimal residues are left. An established new safe level for KBrO3 of 20 ppb or 0-60 mg/kg in flour has been issued by the World Health Organization to ensure the safety of bread consumers. This study investigated the presence of KBrO3 in selected pan de sal bread, one of the staple food in the Fillipinot diet. Bread samples were purchased from five randomly selected bakeries. Test liquids were extracted from the bread, and the solutions underwent purification and recrystallization to obtain bromate in its purest form. The mean amount of bromate was then measured and teh variance between groups was analyzed using 2-way ANOVA. Results showed that potassium bromate was found to be present in all bread samples from the different bakeries, but in levels lower than the required limit by WHO. This means that even if bromate was present, bread sold in Iloilo City is still safe for purchasing and consumption by consumers.
Research II : Research Manuscripts
Keywords: Potassium Bromate